Three-dimensional dynamic response of infinite plate resting on multilayered orthotropic foundation under moving loads - Chun-Li Zhang; Meng Cao; Long Hong; Yun-fei Qi (PLoS ONE, 2026)
In response to the dynamic response of layered foundation pavement structures caused by traffic loads, a three-dimensional coupled model of an infinite elastic plate on an orthotropic layered foundation under moving loads is established. Based on elastodynamic theory and Kirchhoff thin-plate theory, governing equations are derived by introducing a moving coordinate system and incorporating orthotropic constitutive relations. Through double Fourier transforms and matrix analysis, a single-layer foundation transfer matrix is formulated. The global stiffness matrix is assembled using interlayer continuity conditions, ultimately yielding an analytical solution for the dynamic response of the plate and foundation in the integral transform domain. Combined with ABAQUS finite element simulations, the effects of foundation stratification, soil orthotropy, load parameters, and plate parameters on the dynamic response are systematically studied. The results indicate that the layering of the foundation significantly affects the plate deflection. The orthogonal anisotropy of the first soil layer has a more significant impact on deflection compared to isotropic conditions, and this characteristic needs to be considered in practical engineering. The increase in load speed leads to an increase in peak deflection, while the increase in load frequency results in a decrease in peak deflection. Optimization of plate parameters can effectively suppress deformation, and the amplitude of the deflection curve decreases with the increase of the elastic modulus or thickness of the plate.